Design and Construction of an Internet of Things (IoT)-Based Smart Garden System - Badriana Badriana; Putri Ramadhani; Muhammad Hidayat; Sebastian Ferdi Caras Sinuhaji; Darmeli Nasution; Aprina Br Surbakti (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
The use of the Internet of Things is currently very useful for the plantation sector, especially mustard greens. The Smart Garden System is still not widely found on plantation land. Smart Garden comes from English which means garden or smart garden, which is a system design created to make work in plantations easier. The aim of making this tool is to help in managing the plants, apart from helping in managing the plants, this Smart Garden can also be used to measure the humidity/air content in the soil, because some people who are cultivating do not know/cannot distinguish which soil is good for certain crops are planted and which are not, resulting in many crops failing to harvest and being detrimental because they wither and die. So it is hoped that this smart garden system can help many farmers in maintaining soil moisture conditions and can minimize damage to plants. "Smart Garden System" Refers to the concept of technology integration in garden or agricultural management to increase efficiency, productivity and loss. This Smart Garden System uses an ESP32 Microcontroller as data processing and control for Soil hygrometer, LED, 16x2 LCD, Water Washer and other components. REFERENCESAbdullah, R. (2021). 7 in 1 pemrograman web untuk pemula. PT Elex Media Komputindo.Abdur Rochman, M. I., Hanafri, M. I., & Wandira, A. (2020). Implementasi website profil SMK Kartini sebagai media promosi dan informasi berbasis open source. Academic Journal of Computer ScienceResearch (AJCSR), 2(1), 1–6. https://ajcsr.ejournal.id/ajcsr/article/view/33Adani, M. R. (2020). Mengenal apa itu internet of things dan contoh penerapannya.https://www.sekawanmedia.co.idAli, M. M., Sukaca, G., & Aji, Z. P. (2020). Pengaruh ketahanan insulasi pada lampu LED swabalastterhadap keselamatan pengguna sesuai SNI IEC 62560. Jurnal Teknik Elektro dan Komputer, 9(2),80–86.Anwar, A., et al. (2020). Sistem pendeteksi kandungan nutrisi dalam tanah berdasarkan warna dankelembapan menggunakan metode Naive Bayes. Jurnal Pengembangan Teknologi Informasi dan IlmuKomputer, 4(8), 2763–2770. https://j-ptiik.ub.ac.id/index.php/j-ptiik/article/view/8021Chabir, S. O., & Kunang. (2020). Prototype smart garden system berbasis mikrokontroler. Bina DarmaConference on Engineering Science, 2, 10–19.Darmawan, I. W. B., Kumara, I. N. S., & Khrisne, D. C. (2022). Smart garden sebagai implementasisistem kontrol dan monitoring tanaman berbasis teknologi cerdas. Jurnal SPEKTRUM, 8(4), 161–168.https://doi.org/10.24843/SPEKTRUM.2022.v08.i04.p05De, A., & Singh, R. (2020). Organic production of Cymbidium orchids. Acta Scientific Agriculture, 4(3),17–21. https://doi.org/10.31080/ASAG.2020.04.0812Efendi, Y. (2018). Internet of things (IoT): Sistem pengendalian lampu menggunakan Raspberry Piberbasis mobile. Jurnal Ilmiah Ilmu Komputer, 4(2), 7–12.https://ejournal.unira.ac.id/index.php/jikom/article/view/191Gulo, S., & Simamora, R. J. (2020). Perancangan sistem informasi administrasi rawat inap dan rawatjalan pada Rumah Sakit Umum Siti Hajar. Methomika: Jurnal Manajemen Informatika &Komputerisasi Akuntansi, 2(1), 30–42. https://doi.org/10.33365/methomika.v2i1.527Gunawan, I., Ahmadi, H., & Said, M. R. (2021). Rancang bangun sistem monitoring dan pemberi pakan otomatis ayam anakan berbasis internet of things. Infotek: Jurnal Informatika dan Teknologi, 4(2),151–162. https://doi.org/10.29408/jit.v4i2.4707Hu, A. Q., & Yahya. (2020). Rancang bangun aplikasi perpustakaan menggunakan frameworkCodeIgniter. Jurnal Sistem Informasi dan Sains Teknologi, 2(2), 45–51.Jordy, A. B. (2021). Rancang bangun dan analisis kinerja perangkat transceiver sistem visible lightcommunication (Skripsi sarjana). Universitas Telkom.Lestari, K. C., & Amri, A. M. (2020). Sistem informasi akuntansi. Deepublish.Maydianto, & Ridho, M. R. (2021). Rancang bangun sistem informasi point of sale dengan frameworkCodeIgniter. Jurnal Comasie, 2, 50–59.Mulyanto. (2020). JINTEKS: Jurnal Inovasi Teknik dan Sistem Komputer, 2(1).Nistrina, K., & Rahmania, A. (2021). Sistem informasi point of sale berbasis website. Jurnal SistemInformasi, 3(2), 56–63.Rajkumar, B., et al. (2020). Internet of things: Principles and paradigms. Elsevier.https://doi.org/10.1016/C2018-0-01735-5Retno, D., Zain, H., Ipriadi, E. P., & Rahmawati, S. (2021). Teknologi internet of things dalampenyemprotan insektisida aglonema pada greenhouse. Jurnal Teknologi, 11(2), 36–43.https://doi.org/10.31849/jtek.v11i2.6782Romli, I., Hugo, K. L. N., & Afriantoro, I. (2021). Perancangan dan implementasi smart garden berbasisinternet of things pada perumahan Central Park Cikarang. Indonesian Journal of Business Intelligence,4(2), 42–52. https://doi.org/10.21927/ijubi.2021.4(2).42-52Sasmito, G. W., & Wijayanto, S. (2020). Studi pengenalan internet of things bagi guru dan siswa SMK.Dinamisia, 4(1), 186–194. https://doi.org/10.31849/dinamisia.v4i1.3757Solichin, A. (2021). Pemrograman web dengan PHP dan MySQL. Universitas Budi Luhur.Taufik, M., Misbahuddin, & Nrartha, I. M. A. (2021). Sistem monitoring dan kontrol penerangan jalan umum berbasis LoRa. DIELEKTRIKA, 8(2), 95–102. https://doi.org/10.31849/dielektrika.v8i2.6772V. Muthusamy, et al. (2021). IoT in 2021: Trends, challenges, and opportunities. Future Internet, 13(12), 324. https://doi.org/10.3390/fi13120324Yudhanto, Y., & Aziz, A. (2020). Pengantar teknologi internet of things. UNS Press.Yunia, R. A., & Wardiyati, T. (2020). Pengaruh pH tanah dan pupuk NPK terhadap pertumbuhan danwarna bunga hortensia. PLANTROPICA: Journal of Agricultural Science.